Effects of the valsartan/amlodipine combination and nifedipine gastrointestinal therapeutic system monotherapy on brachial pulse pressure and radial augmentation index in hypertensive patients. Issue 4 (August 2021) - Xu, Shao-Kun; Zeng, Wei-Fang; Li, Yan; Chen, Liang-Long; Xie, Jian-Hong; Wang, Ji-Guang
Abstract : Objective: In a substudy of a randomized controlled trial, we investigated the effects of the valsartan/amlodipine single-pill combination and nifedipine gastrointestinal therapeutic system (GITS) monotherapy on brachial pulse pressure (bPP) and radial augmentation index (rAI) in patients with previously uncontrolled hypertension. Methods: We performed measurements of clinic blood pressure (BP) and pulse rate and rAI ( n = 63) and ambulatory BP monitoring ( n = 42) at baseline and 12-week of follow-up. Analysis of covariance was performed to calculate the least square mean change from baseline and between-group differences [95% confidence interval (CI)]. Correlation analysis was performed to study the interrelationship between the changes in bPP and rAI and in pulse rate. Results: After 12-week treatment, clinic and ambulatory SBP/DBP and pulse rate were not differently changed between the valsartan/amlodipine ( n = 29) and nifedipine GITS groups ( n = 34, P ≥ 0.06) except daytime SBP ( P = 0.01). The reductions in 24-h and daytime ambulatory bPP were significantly greater in the former than the latter group ( P ⩽ 0.04). rAI increased slightly by 3.5% ( P = 0.20) and 5.2% ( P = 0.06) in the valsartan/amlodipine and nifedipine groups, respectively, with a between-group difference of −1.7% (95% CI −9.6 to 6.1%, P = 0.66). In the two groups combined, the changes in clinic and ambulatory bPP were not or weakly associated with that in clinic or ambulatory pulse rate ( r = −0.14 to 0.36, P = 0.02–0.95), while the changes in rAI were more strongly or significantly associated with that in clinic or ambulatory pulse rate ( r = −0.39 to −0.23, P = 0.02–0.16). Conclusions: Antihypertensive drug-induced changes in rAI but not bPP were dependent on pulse rate.